PENATAAN KAWASAN WISATA BENDUNGAN PAGUYAMAN DI KECAMATAN WONOSARI DENGAN PENDEKATAN ARSITEKTUR EKOLOGI - Djailani, Zuhriati A.; Wiranatha, I Gede (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2024)
Tourism is a development sector that has become the focus of the Indonesian government because it plays a crucial role in the country’s progress, especially as a foreign exchange contributor. As one of the important economic sectors, tourism not only drives the economy but also serves as an effective means to reduce unemployment rates. One of the potential tourist attractions in Gorontalo is the Paguyaman Dam. This dam offers beautiful natural scenery, often utilized by the community for recreation and tourism. However, using the Paguyaman Dam as a tourist attraction has not gotten serious attention from the local government,necessitating improvements in various aspects such as area development, facility provision, and enhancement of supporting infrastructure. Applying the ecological architecture approach, the design concept adapts to the climate and surrounding environment, optimizes low energy use,and utilizes existing resources. The focus of developing the Paguyaman Dam tourism area aims to provide facilities that support tourism and recreational activities there. This research employs a descriptive qualitative method, with primary and secondary data, involving direct observation,interviews, literature studies, book references, journals, and online sources. The collected data are analyzed to produce a design concept that adheres to applicable regulations. The results of this report are a design concept that can serve as a guide for continuing the development of the Paguyaman Dam tourism area.